Fragment size, pollination efficiency and reproductive success in natural populations of wind-pollinated Polylepis australis (Rosaceae) trees - Seltmann, Peggy (2007)
It is well known that habitat fragmentation is likely to negatively affect the reproductive success of a species. Despite this fact, studies on the effects of fragmentation on reproductive success in combination with effects on natural pollination of wind-pollinated tree species are very rare. In this study, we analyzed the relationships between fragment size, components of pollination efficiency, reproductive success and progeny vigour of the highly fragmented populations of the wind-pollinated treeline species Polylepis australis (Rosaceae) in Argentina. We conducted our study in the high mountains of Córdoba, comparing pollination efficiency and reproduction between four fragment sizes. Most of our results indicate that P. australis is currently insensitive to fragmentation. However, our study revealed also a linear increase in leaf area and biomass of 40-day-old seedlings with increasing fragment size. Inbreeding problems through fragmentation as well as decreased habitat quality in small fragments are discussed as possible causes for the impaired progeny vigour.